Joint British Societies' guideline on management of cardiac arrest in the cardiac catheter laboratory. Issue 12 (25th April 2022) - Dunning, Joel; Archbold, Andrew; de Bono, Joseph Paul; Butterfield, Liz; Curzen, Nick; Deakin, Charles D; Gudde, Ellie; Keeble, Thomas R; Keys, Alan; Lewis, Mike; O'Keeffe, Niall; Sarma, Jaydeep; et al.
Abstract : More than 300 000 procedures are performed in cardiac catheter laboratories in the UK each year. The variety and complexity of percutaneous cardiovascular procedures have both increased substantially since the early days of invasive cardiology, when it was largely focused on elective coronary angiography and single chamber (right ventricular) permanent pacemaker implantation. Modern-day invasive cardiology encompasses primary percutaneous coronary intervention, cardiac resynchronisation therapy, complex arrhythmia ablation and structural heart interventions. These procedures all carry the risk of cardiac arrest. We have developed evidence-based guidelines for the management of cardiac arrest in adult patients in the catheter laboratory. The guidelines include recommendations which were developed by collaboration between nine professional and patient societies that are involved in promoting high-quality care for patients with cardiovascular conditions. We present a set of protocols which use the skills of the whole catheter laboratory team and which are aimed at achieving the best possible outcomes for patients who suffer a cardiac arrest in this setting. We identified six roles and developed a treatment algorithm which should be adopted during cardiac arrest in the catheter laboratory. We recommend that all catheter laboratory staff undergo regular training for these emergency situations which they will inevitably face.